2008
DOI: 10.1136/adc.2007.119826
|View full text |Cite
|
Sign up to set email alerts
|

Are universal standards for optimal infant growth appropriate? Evidence from a Hong Kong Chinese birth cohort

Abstract: Although the WHO study group concluded there was a striking similarity in length/height among different populations, Hong Kong Chinese toddlers are, on average, shorter. Epigenetic constraints on growth coupled with the rapid epidemiological transition in Hong Kong may not have allowed sufficient generations for infants and children to reach their full genetic height potential, and with it the WHO standards. A universal infant growth standard may not be appropriate across all populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
59
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 33 publications
3
59
0
5
Order By: Relevance
“…[11][12][13] Results from these studies showed that our newborns have smaller birth parameters compared to the WHO standard. For example, Japanese breastfed infants are significantly shorter and lighter throughout almost the first 24 months 12 compared to the WHO growth standard, and infants in Hong Kong are shorter at 36 months.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…[11][12][13] Results from these studies showed that our newborns have smaller birth parameters compared to the WHO standard. For example, Japanese breastfed infants are significantly shorter and lighter throughout almost the first 24 months 12 compared to the WHO growth standard, and infants in Hong Kong are shorter at 36 months.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, studies from the East Asian countries have demonstrated a trend of smaller head circumference and birth weight. 12,13 Similarly, a Malaysian study in 1994 revealed that Malaysian infants were smaller than the standard reference. 8 The predictors of head circumference of infants have been widely studied.…”
mentioning
confidence: 99%
“…According to this new chart reference, it is widely accepted that an international reference is useful, since the increase in height and weight of well-fed, healthy children younger than 5 years from different ethnic backgrounds and different continents is reasonably similar. Nevertheless, this supposition continues to be controversial (Hui et al 2008). Some limitations to our study are related to the crosssectional method, the small sample size of each group, and the non-paired Peruvian preschool controls.…”
Section: Discussionmentioning
confidence: 87%
“…The WHO child growth charts were updated with new international growth standard statistical distribution in 2006 for the growth of healthy children living under optimal conditions [9]. The use of both WHO and CDC growth charts are intended for all children regardless of socioeconomic status and ethnicity, however there are studies to suggest that they may not be suitable for all populations [10,11]. In recent studies, there are researchers that questioned whether the uses of WHO growth standards are applicable for a Chinese population, specifically for children in Hong Kong [12].…”
Section: Discussionmentioning
confidence: 99%
“…In recent studies, there are researchers that questioned whether the uses of WHO growth standards are applicable for a Chinese population, specifically for children in Hong Kong [12]. Based on the 1997 Hong Kong birth cohort as the population based study -they found that the weight for age was close to the 50 th percentile of the WHO standards for both boys and girls before 3 years of age, however, toddlers at age of 3 were on average, shorter [11]. Similarly, in Hong Kong, the Body Mass Index (BMI) of Chinese and Caucasian infants was assessed and it was evident that ethical differences between populations exists [13].…”
Section: Discussionmentioning
confidence: 99%